Perturbations in Microbial Communities at Hydrothermal Vents of Panarea Island (Aeolian Islands, Italy) - Annamaria Gallo; Fabio Sposito; Manfredi Longo; Gianluca Lazzaro; Cinzia Giuseppina Caruso; Sabina Morici; Sergio Scirè Scappuzzo; Slobodanka Radovic; Valeria Villanova; Luca Vecchioni; Marco Arculeo; Rosa Alduina (Biology)
Marine hydrothermal ecosystems represent extreme environments connected to submarine volcanic areas characterized by vents, having high temperatures and particular chemical compositions. The hydrothermal marine system of Panarea, located in one of the seven small islands belonging to the Aeolian Archipelago (southern Tyrrhenian Sea), is characterized by a range of vents exhibiting diverse physical and chemical conditions. We aimed to analyze the microbial community of a peculiar hot spring belonging to the Panarea hydrothermal field, known as “Black Point” (BP), in two separate sampling expeditions (May and August). Our results demonstrated that the chemical–physical variations within this hydrothermal vent, such as temperature fluctuations, mineral content, and hydrothermal fluid dynamics, play a role in shaping the structure and diversity of microbial communities. The differences between the two sampling expeditions suggest that seasonal changes, i.e., in temperature, pH, and redox potential (Eh), could drive microbial community shifts over time.